AFRICAN UNION, STATE-BUILDING AND THE CHALLENGES OF STATE FRAGILITY IN AFRICA - Nwozor, Agaptus (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This article evaluates the transformational role of the African Union (AU) in enhancing state-building and reversing the fragility of African states. Essentially, the AU was repackaged in July 2001 as a strategic platform to meet new aspirations for African unity and development. This article notes that after over half a century of collective African attempt at strengthening its state system, the picture is still one of fragile statehood, thus emphasizing the imperative of evolving new strategies to reverse the forces of state fragility in the continent. The article contends that in the face of concerns for African development within the context of sustainable development goals (SDGs), a healthy and functional state system is an irreducible minimum requirement. In order to repair the seemingly battered image of statehood in Africa, the AU must contend with, and overcome, the interplay of internal and external forces that conduce to and trigger fragility.